Labeling of OTC Drugs in India: Dilemma Whether Pharmacy Centred or Patient Centred - Shankar, Ravi; Joshi, Monika; Pathak, Kamla (Indian Journal of Pharmacy Practice)
Context: OTC medicines are an important component in healthcare, allowing the freedom to the patient to selfmedicate for treating minor, common health problems, at lower costs and with higher time saving. It is very important that the patients have access to sufficient information to make an informed choice for the proper use of these medicines. The label of OTC medicines plays an important role in conveying valuable information to the patient for safe and effective use of OTC. Objective: The study was conducted to evaluate the labelling of OTC drugs in India as per the guidelines of US FDA. Result: The result was not positive as it was found that 59% of the labels did not disclose even the therapeutic category. There are 87% labels which do not have any information related to the contraindications and 90% labels do not enumerate the adverse effects of the medicine. The legibility was very poor comprising only 33% of total. Conclusion and Practice Implication: The labels were not able to withstand the guidelines of US FDA that may be compromising with the health and safety issues of the patients. The labels should provide all important information and instructions to patient.
Keywords: Over the counter medications; USFDA; primary labels; patient package inserts; Indian scenario